DEVELOPMENT OF STUDENTS’ CREATIVE ABILITIES IN FINE ARTS LESSONS (International conference on multidisciplinary science, 2023)
The article talks about the development of students' creative abilities in fine arts lessons, and also talks about the process of organizing activities, highlighting some points.